A Modified Electrosurgery Unit Based on High Frequency Design with Monopolar and Bipolar Method - Rafsanzani, Edo; Pudji, Andjar; Indrato, Tri Bowo; Yan, Shengjie; Bogavev, Sergey A. (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2021)
The purpose of this study is to design a tool that is used to replace a conventional scalpel with a tool that utilizes high frequency in order to eliminate faradic effects on body tissues where the high frequency will be adjusted to the duty cycle which aims to obtain various types of surgery required by doctor. That makes the Electrosurgery Unit is important to build because it can cause loss of a lot of blood during surgery less than using a conventional scalpel. Electrosurgery Unit can also be used for coagulation which means some surgery doesn’t just need dissection but also seal some tissue to reduce or cut loss of some diseases at the patient. The result of the high frequency which is regulated by the duty cycle, will then be centered at one point on an object. In this study, the researchers took advantage of the type of heat effect produced by high frequencies, which were concentrated at one point so that it could be used to carry out the process of surgery (cutting) and coagulation (coagulation) on body tissues so as to minimize the occurrence of large blood loss. The researcher took advantage of the high frequency of 400 kHz generated by the oscillator circuit and then set it with a duty cycle program on the Arduino of 6% on 94% off for coagulation and 100% on for cutting. The module design consists of a 400 kHz frequency generator, a pulse control circuit to adjust the duty cycle, a power control circuit as a power setting, a driver circuit to combine the frequency with the set power so that different outputs are obtained according to the settings, an inverter circuit to increase the voltage. and an interlock circuit as a bipolar and monopolar output separator